HUMAN IMMUNODEFICIENCY VIRUS, HEPATITIS B VIRUS AND SYPHILIS INFECTIONS AMONG LONGDISTANCE TRUCK DRIVERS IN, A PORT CITY IN GHANA - Adjei, Andrew A.; Atta, Priscilla Boahema; Krampa, Francis; Lartey, Margaret; Nii Trebi, Nicholas; Abdul Rahman, Mubarak; Agyemang, Seth; Adiku, Theophilus K.; Tettey, Yao; Gyasi, Richard K. (African Journal of Infectious Diseases (AJID), 2015)
Background: Although the high prevalence of human immunodeficiency virus (HIV), hepatitis B virus (HBV) and syphilis infections among longdistancetruck drivers has been well documented globally, such data are sparse from Africa, and there has been no such data from Ghana. This studycarried out between the months of January and June 2013 sought to determine the sero-prevalence and risk factors of HIV, HBV and syphilisinfections among long distance truck drivers at the Tema sea port, Ghana.Materials and Methods: Of a total of 800 eligible drivers, 106 (13.25%) drivers consented to take part in the study. Subjects voluntarily completed arisk factor questionnaire and provided blood specimen for testing for HIV, syphilis and the surface antigen of HBV (HBsAg).Results: The mean age of the drivers was 40.56 ± 11.56 years. The sero-prevalence of HIV was 0.94%, 14.2% had HBsAg and reactive syphilisserology was 3.8%. On multivariate analysis, the main determinants of HBV infection were; multiple sexual partnership (OR, 6.36; 95% CI: 1.35–29.79), patronage of commercial sex workers (OR, 6.85; 95% CI: 0.88 – 52.89), cross-border travelers (OR: 6.89-fold, 95% CI: 0.86 - 55.55) andprolonged duration of trips for more than two weeks (OR: 4.76; 95% CI: 0.59 – 38.02). The main determinant of syphilis infection on multivariateanalysis was being a Muslim (OR, 2.19; 95% CI: 0.22 – 21.74).Conclusion: The data indicate a lower sero-prevalence of HIV but a higher sero-prevalence of syphilis. However, the sero-prevalence of HBVinfection is comparable to that of the general population.